The acceptance of children in stories book of Malaysian folkore (case study on the acceptance among children towards Malaysian folklore storybook in city of Malacca) / Nur Sabrina Zulkarnain - Zulkarnain, Nur Sabrina (2014)
Folklore generally refers to the traditions which may include the music, storytelling, popular beliefs and customs practice of a community. Many of us grow up on a steady diet of fairy tales Cinderella, Snow White, Rapunzel and Red Riding Hood are some of the stories that, have timeless and universal appeal. Previously read to children, they have now been adapted into television shows and movies. The apparent success of Walt Disney's productions of many of these fairy tales contributes to the immortality and universality of their appeal to people. They are metaphorical stories that stemmed from basic human experiences and contained vital information that strengthened the common bonds of people living in communities. At the surface level, fairy tales are entertaining stories of magic, lush landscapes, beauty, wealth, blissful marriages. Upon'further scrutiny, however, our folklore also had that. Unfortunately, our children did not appreciate our own folklore. In order to make the children attract in reading book of our own folklore this paper looks at the extent to which literature for children has developed through the years to provide a rich ground for the enrichment of children's literacy in Malaysia. Malay folklore stories have many of interesting stories. However most of the young generation nowadays has a lack of knowledge and awareness about the other Malay's folklore stories. Thus, the aim of this ,research is to study and analyze the acceptance among. children towards Malaysian folklore story book in city of Malacca. In this context, the researcher intends to understand the acceptance among the children regarding the storybook of Malaysian folklore and western fairy tale. In addition, the study also wants to analyze the children's general knowledge and perception about the Malaysian Folklore. Generally, this research is a case study among the certain group of people. In order to obtain the data, the researcher frequently used a qualitative research method to observe the scenarios that are related to the topic.Thus, reliable information was gathered from the books, articles and internet in order to analyze the literature reviews of the study. Besides, the researcher also used a quantitative research method to gain the raw data about her respondents. The researcher used survey questionnaires as an instrument to collect the data. Lastly, observation and an interview also used in order to analyze the children's behavior towards acceptance on storybook.